2020
DOI: 10.3390/jcm9041033
|View full text |Cite
|
Sign up to set email alerts
|

Residual Inflammation Indicated by High-Sensitivity C-Reactive Protein Predicts Worse Long-Term Clinical Outcomes in Japanese Patients after Percutaneous Coronary Intervention

Abstract: The aim of this study was to investigate the long-term clinical impact of residual inflammatory risk (RIR) by evaluating serial high-sensitivity C-reactive protein (hs-CRP) in Asian patients with coronary artery disease (CAD). We evaluated 2032 patients with stable CAD undergoing percutaneous coronary intervention (PCI) with serial hs-CRP measurements (2 measurements, 6–9 months apart) from the period 2000 to 2016. A high-RIR was defined as hs-CRP > 0.9 mg/L according to the median value. Patients were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…A recent analysis from Japan showed that a persistent high RIR phenotype (serial hsCRP measurements > 0.9 mg/L: baseline and 6-9 months apart) in patients with stable CAD was significantly associated with MACE at 5year follow-up (HR: 2.22; 95%: CI 1.37 to 3.67; P = 0.001). 22 In the present study after 1-month of the recommended medical therapy, the decrease in hsCRP level was greater in AMI vs. non AMI patients 4 . This finding may suggest that longterm prognosis past the acute phase in AMI patients can be more accurately predicted by hsCRP level at the late time point, rather than the index hsCRP level.…”
Section: Time-dependent Change Of Inflammation Status In Cad Patientssupporting
confidence: 41%
See 2 more Smart Citations
“…A recent analysis from Japan showed that a persistent high RIR phenotype (serial hsCRP measurements > 0.9 mg/L: baseline and 6-9 months apart) in patients with stable CAD was significantly associated with MACE at 5year follow-up (HR: 2.22; 95%: CI 1.37 to 3.67; P = 0.001). 22 In the present study after 1-month of the recommended medical therapy, the decrease in hsCRP level was greater in AMI vs. non AMI patients 4 . This finding may suggest that longterm prognosis past the acute phase in AMI patients can be more accurately predicted by hsCRP level at the late time point, rather than the index hsCRP level.…”
Section: Time-dependent Change Of Inflammation Status In Cad Patientssupporting
confidence: 41%
“…A recent analysis from Japan showed that a persistent high RIR phenotype (serial hs-CRP measurements >0.9 mg/L: baseline and 6–9 months apart) in patients with stable CAD was significantly associated with MACE at 5-year follow-up (HR: 2.22; 95%: CI 1.37–3.67; p = 0.001). 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical studies have shown that a number of patients still have a residual risk for cardiovascular disease even after achieving the targeted cholesterol level 27. It has been documented that inflammation indicators play a dominant role in the poor prognosis of CAD in patients with a targeted LDL-C level 28 29. Therefore, residual inflammatory risk has gained much interest in patients with controlled cholesterol 30.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with acute myocardial infarction (AMI) undergoing PCI, inflammatory response plays a pivotal role in the whole pathophysiological process. Since inflammation can promote endothelial cell injury ( 4 ), vascular remodeling ( 5 ), and plaque destabilization ( 6 ), it is now regarded as another risk factor for AMI besides traditionally acknowledged risk factors like hypertension and dyslipidemia ( 7 ). In addition, the pro-inflammatory response occurs in the early stage of AMI and may exacerbate after PCI, thus contributing to the death of myocardial cells ( 8 ).…”
Section: Introductionmentioning
confidence: 99%